Edukasi Penanggulangan Banjir Melalui KKN Mahasiswa Stisipol Candradimuka, Di Kelurahan Sako Untuk Mewujudkan Program Kampung Iklim Sigap, Cerdas Dan Sehat - Ardiansyah (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Indonesia is a country that is prone to natural disasters. Almost all types of disasters that have occurred in Indonesia. Indonesia is ranked fifth in the world for the highest number of deaths caused by natural disasters. This is an "alarm" for our community to be friendly with disasters by acting in response to disasters. Many natural disasters that can occur include floods. Floods are the most common natural threat and the most detrimental, both in terms of humanity and the economy. However, there is still very little understanding and awareness of the community in Sako Komplek Bumi Sako Damai (BSD) Village, precisely in RT.097 RW.037 The location is densely populated with a number of family heads (KK) 150. Therefore, it is necessary to increase understanding about the impact of flood disasters and the importance of preventing floods. Activities carried out using the Covid Education method for the Community RT.097 RW.037 Kelurahan Sako Komplek Bumi Sako Damai (BSD). The KKN program begins with mutual cooperation activities that support airways, prevention of covid by providing masks and hand sanitizer, construction of trash cans and installation of disinfectant banners as well as education on healthprotocols.